Digital Fatigue among Students in Higher Education: Effects on Online Arabic Learning and Coping Strategies - Anwar Sanusi; Kemas Abdul Hai; Neldi Harianto; Arum Gati Ningsih; Kiki Cahya Muslimah (LISANIA: Journal of Arabic Education and Literature, 2025)
This study explores symptoms of digital fatigue among students and its impact on the effectiveness of online Arabic learning in higher education, while also identifying learners’ coping strategies. Using a mixed-methods exploratory design, participants were students of an Arabic Language Education program at a state university in Jambi Province, selected through purposive sampling. Data were collected through semi-structured interviews, online class observations, an adapted Fatigue Assessment Scale (FAS), and LMS documentation. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were processed descriptively. The findings show that digital fatigue manifested as visual strain when reading Arabic texts, decreased focus during synchronous sessions, and weak vocabulary retention due to limited oral interaction. These symptoms reduced learning effectiveness, reflected in low participation, shallow text engagement, and irregular task submission. Students developed coping strategies such as balancing online–offline study routines, rewriting notes manually, using supportive applications, peer collaboration, and relying on lecturer flexibility. The study concludes that effective online Arabic instruction requires alignment between pedagogical design, cognitive load management, and social connectedness, and recommends integrating microlearning, retrieval practice, and community-based learning to reduce digital fatigue and sustain engagement.